Studies on preparation and storage of tamarind squash - K Laxman, P Archana, (Journal of Spices and Aromatic Crops, 2015)
An attempt was made to standardize the protocol for the preparation of tamarind squash. The chemical composition of tamarind squash and changes in chemical constituents during storage at ambient temperature were studied. Results showed that higher amount of mean TSS (54.13%), reducing sugar (9.51%) and total sugar (30.25%) were noticed in recipe having 30% juice + 50% TSS + 1% acidity, whereas higher retention of ascorbic acid (3.68 mg 100 g-1) was observed in recipe having 30% juice + 40% TSS + 1% acidity. However, minimum TSS (40.48%), reducing sugar (8.82%) and total sugar (22.77%) were noticed in recipe having 25% juice + 40% TSS + 1% acidity and titrable acidity in the recipe having 30% juice + 50% TSS + 1% acidity. Among the recipes the tamarind squash prepared from 30% juice + 50% TSS + 1% acidity was found superior to other recipes. The beverage retained its characteristic colour, aroma and taste up to 3 months of storage at room temperature.